Palm oil : production, processing, characterization, and uses - Lai, Oi-Ming; Tan, Chin-Ping; Akoh, Casimir C., 1955- (AOCS Press, 2012)
This book serves as a rich source of information on the production, processing, characterization and utilization of palm oil and its components. It also includes several topics related to oil palm genomics, tissue culture and genetic engineering of oil palm. Physical, chemical and polymorphic properties of palm oil and its components as well as the measurement and maintenance of palm oil quality are included and may be of interest to researchers and food manufacturers. General uses of palm oil/kernel oil and their fractions in food, nutritional and oleochemical products are discussed as well as the potential use of palm oil as an alternative to trans fats. Some attention is also given to palm biomass, bioenergy, biofuels, waste management, and sustainability.